If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 2s + -66 Reorder the terms: 13 = -66 + 2s Solving 13 = -66 + 2s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-2s' to each side of the equation. 13 + -2s = -66 + 2s + -2s Combine like terms: 2s + -2s = 0 13 + -2s = -66 + 0 13 + -2s = -66 Add '-13' to each side of the equation. 13 + -13 + -2s = -66 + -13 Combine like terms: 13 + -13 = 0 0 + -2s = -66 + -13 -2s = -66 + -13 Combine like terms: -66 + -13 = -79 -2s = -79 Divide each side by '-2'. s = 39.5 Simplifying s = 39.5
| 2p-5+2p=35 | | 2.48=3.1z | | 18-9x=21x-22 | | 3.72=y/1.5 | | I-15=-22 | | X^6-25=0 | | 7.2y-3.25=17 | | 0.4(2n-3)=0.2n | | (6x^2-53x-10)/(x-8) | | -10p+15=-25 | | 500=30x+2.50(x-150) | | 8(2-2k)+8(8k+3)=-56 | | a=1/2(16x18) | | 8(3x+4)-2x-5-7x=20 | | 8x+3(2x+1)=7 | | 5k-3k=-6 | | 6p-12=-6 | | -21=(19/-3)+3 | | 40x-25y= | | n-(-1)=-87 | | 5x-x=-q | | 2e-4e=16 | | 4/(v-5)=-3 | | 4x^2=9/16 | | t^2-4t+16=0 | | 3/13=u/11 | | 6x-6x= | | 3x^3-12x^2+2x-8=0 | | 9x^2-x+7=0 | | 4/v-5=-3 | | a-(-2)=7 | | 2(x+3)-4=-6 |